OP16 Utilising a Novel Framework to Assess Public Health Nutrition Actions Across 30 European Countries (EuroHeart II Project). (10th September 2013) - Bromley, H; Williams, F Lloyd; Orton, L; McGill, R; Anwar, E; Moonan, M; Robinson, D Taylor; Calder, N; O'Flaherty, M; Castillo, M Guzman; Hawkes, C; M, Rayner; et al.
Abstract : Background: EuroHeart II is a European programme designed to inform cardiovascular health strategies across Europe. Our project examines the role of food policies in cardiovascular disease prevention, including the development and piloting of a novel conceptual framework for categorising public health nutrition policies. Methods: We conducted a mapping exercise to identify and categorise public health nutrition policy actions across 30 European countries using a novel framework. The framework was based on the traditional marketing "4Ps" approach: Price, Product, Promotion and Place (the "marketing mix"). A database was created to summarise public health nutrition policy for 30 European countries (EU 27 plus Iceland, Norway and Switzerland). National policies were classified according to Price (taxes, subsidises, other economic incentives); Product (reformulation, new healthier products); Place (schools, workplaces, community settings); and Promotion (advertising to children/general population, food labelling and health education initiatives). Results: Dialogue, recommendations and nutrition guidelines are now widespread across Europe. Information and education campaigns are also widespread. These include campaigns covering the general population, and campaigns targeting schools, the workplace or communities. Subsidies for fruit in schools are almost universal through the EU School Fruit Scheme, but implementation differs across the 30 countries. New EU legislation supports limited, back of pack food labelling. Some countries have also implemented national legislation requiring more detailed label information about the nutritional value of foods (e.g. Finland). However, the presentation and information vary widely. Voluntary reformulation of foods is common, especially for salt, sugar and total fat (e.g. salt reduction in the UK). However, mandatory reformulation of products to reduce saturated fat and salt are still limited to trans fat bans in Austria, Denmark, Iceland and Switzerland. Legislation/regulation affecting salt, sugar, fat and fruit and vegetable consumption is uncommon, although several countries have legal requirements regarding the maximum salt content in certain foods (Belgium, Bulgaria, Finland, Greece, Latvia, Lithuania, Netherlands, Portugal, Romania, Slovak Republic, Slovenia and Wales). Taxes to promote healthy nutrition are currently used infrequently. However, Finland, France, Hungary and Portugal have implemented 'sugar taxes' on sugary foods and sugar-sweetened beverages. Hungary and Portugal also tax salty products. Conclusion: The diverse public health nutrition activities across 30 European countries might initially appear complex and bewildering. However, the "4Ps" framework offers a potentially structured and comprehensive categorisation of these diverse interventions. National food policies in Europe are currently at very different stages of development and implementation. However, exemplar countries might include Denmark, Finland, Hungary, Iceland, the UK and Portugal.